STRATEGIC COST MANAGEMENT AS INSTRUMENT FOR IMPROVING COMPETITIVENESS OF AGRIBUSINESS COMPLEX - Savić, Bojan; Vasiljević, Zorica; Đorđević, Dragan (Economics of Agriculture, 2014)
Cost accounting as a segment of an integrated accounting information system by generation of the relevant information provides significant support for both financial and managerial accounting. The above information represents the information base for decision making of internal and external users (management, investors, creditors and other stakeholders). In this paper a special attention is paid to contemporary systems of cost accounting, the application of which can be seen as an integral part of the effort undertaken in order to measure and control costs, since cost management is one of the indispensable elements to achieve, maintain and improve the competitiveness of enterprises. Having in mind the significant potential the Republic of Serbia has in the field of agricultural production, the aim of this paper is to highlight the challenges and specifics of cost management in the agribusiness complex enterprises. Hence, this paper discusses the modern systems of cost accounting as well as the cost management methods suited to the specific agricultural management activities, which could help to the local companies in efforts for share in the global agri-food products market.